A Systems Framework for Understanding the Environment's Relation to Clinical Teamwork: A Systematic Literature Review of Empirical Studies. Issue 7 (August 2020) - Peavey, Erin; Cai, Hui
Clinician teamwork is effective at improving many health care outcomes, and the physical environment is an important part of a system that facilitates teamwork. This review critically evaluates and synthesizes the empirical evidence on the impacts of the physical environment and surrounding ecosystem on clinician teamwork in health care facilities using a systems-based lens. The systematic search yielded 2, 323 titles and abstracts between 2007 and 2017, which were reviewed and resulted in 34 articles examining physical environment's impact on clinician teamwork. The Systems Engineering for Patient Safety (SEIPS) framework is utilized to thematically structure findings to examine the interdependent nature of built and nonbuilt factors that have a documented impact on clinician teamwork. This study found consistent evidence of the interdependence of these systems factors in facilitating or hampering teamwork, as defined by Salas and colleagues' "Big Five." The review identifies current gaps in the literature and suggests where future research is needed.